Optimal Laparoscopic Management and Oncological Outcomes of Gastrointestinal Stromal Tumors in Duodenum: Pancreaticoduodenectomy or Pancreas-Sparing Duodenectomy? - Lu, Chao (Cancer Manag Res, 2020)
BACKGROUND: Gastrointestinal stromal tumors (GIST) of the duodenum are rarely reported and optimal minimally invasive management has not been well proposed. Pancreaticoduodenectomy and different types of pancreas-sparing duodenectomy can be chosen; however, which to choose and its corresponding clinical outcomes and oncological concerns remain controversial. PATIENTS AND METHODS: Patients diagnosed with GIST of duodenum underwent laparoscopic pancreaticoduodenectomy (L-PD) or pancreas-sparing duodenectomy (L-PSD) in Zhejiang Provincial People's Hospital were enrolled. All prospectively maintained data were analyzed retrospectively. Patients were grouped into the L-PD group or the L-PSD group, and the clinical outcomes and oncological outcomes were analyzed. RESULTS: Between June 2013 and March 2019, a total of 22 patients (11 males/11 females) underwent surgical management, including 13 L-PDs and 9 L-PSDs. The average age was 58.2±9.5 year-old (median 60.5 year-old). The most common presentations were GI bleeding (54.5%) and abdominal discomfort (27.2%), and the dominant lesion located in the second portion of duodenum (59.1%). Compared with L-PD group, L-PSD group showed much shorter operation time (364.2±58.7min vs. 230.0±12.3min, P<0.001), less blood loss (176.9±85.7mL vs. 61.1±18.2min, P<0.001), faster recovery to off-bed (2.6±1.3d vs. 1.1±0.3d, P=0.003), anus flatus (4.5±1.0d vs. 2.4±0.5d, P<0.001) and liquid intake (4.9±1.3d vs. 2.3±0.5d, P<0.001). Lymph node retrieval was much less in L-PSD, but no lymph node metastasis was observed in any patients. L-PSD had much Lower morbidity of both minor (Grade I/II) and major (III/IV/V) complications than that of L-PD (11.1% vs. 61.6%, P=0.02), resulting in shorter hospital stays (10.9±3.8d vs. 20.6±11.1d, P=0.021) and less total cost (76,972.4±11,614.8yuan vs 125,628.7±46,356.8yuan, P=0.006). The median follow-up was 42 months (range from 12 to 82months) without loss. Only 1 L-PD patient suffered hepatic metastasis 36months after surgery, and given sunitinib to stabilize the disease, none of the rest observed recurrence or metastasis. CONCLUSION: For GIST located opposite the major papilla, L-PSD showed comparable safety and oncological benefits when compared to L-PD, with shorter operation time, less blood loss and much faster recovery time, resulting in much less total cost. L-PSD should be applied in selected patients with experienced hands.